La atención integral a la mujer : un compromiso del personal de salud (1999)
ABSTRACT: The present article is divided into two parts. In the first part, the biomedical model as the paradigm that guides health care in the promotion and intervention in women’s health is introduced. The characteristics and points of view of women’s body and health has generated a gap between scientific thought and the women’s own interpretation of health and disease. In the second part, the author proposes to promote women’s health from a gender perspective, with an emphasis in life and health care, to insist on the on integral health care, and to impel self-care as a personal practice and a basic strategy to guide the search of the daily integral welfare. It is concluded that if health professionals include these ideas in their care practices, significant changes will be obtained in their work, thus improving women’s health conditions.